Host resistance to Bacillus thuringiensis is linked to altered bacterial community within a specialist insect herbivore. Issue 21 (5th April 2021) - Paddock, Kyle J.; Pereira, Adriano E.; Finke, Deborah L.; Ericsson, Aaron C.; Hibbard, Bruce E.; Shelby, Kent S.
Abstract: Evolution of resistance to transgenic crops producing toxins from Bacillus thuringiensis (Bt) threatens the sustainability of the technology. Examination of resistance mechanisms has largely focused on characterization of mutations in proteins serving as Bt toxin binding sites. However, insect microbial communities have the potential to provide host resistance to pesticides in a myriad of ways. Previous findings suggest the killing mechanism of Bt relies on enteric bacteria becoming pathogenic in the disrupted gut environment of the insect following Bt intoxication. Thus, here we hypothesized that resistance to Bt would alter the microbiome composition of the insect. Previous studies have manipulated the microbiome of susceptible insects and monitored their response to Bt. In our study, we characterized the associated bacterial communities of Bt‐resistant and ‐susceptible western corn rootworms, a widespread pest of maize in the United States. We found resistant insects harbor a bacterial community that is less rich and distinct from susceptible insects. After feeding on Bt‐expressing maize, susceptible insects exhibited dysbiosis of the associated bacterial community, whereas the community within resistant insects remained relatively unchanged. These results suggest resistance to Bt produces alterations in the microbiome of the western corn rootworm that may contribute to resistance. We further demonstrated that by itself, feeding on Bt toxin‐expressing seedlings caused a shift in the microbiota. This work provides a broader picture of the effect stressors have on microbiome composition, and the potential heritable changes induced as a result of intense selection.